2004
DOI: 10.1111/j.1462-2920.2004.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lime, nitrogen and plant species on bacterial community structure in grassland microcosms

Abstract: SummaryA microcosm-based approach was used to study impacts of plant and chemical factors on the bacterial community structure of an upland acidic grassland soil. Seven perennial plant species typical of both natural, unimproved ( Nardus stricta , Agrostis capillaris , Festuca ovina and F. rubra ) and fertilised, improved ( Holcus lanatus, Lolium perenne and Trifolium repens ) grasslands were either left unamended or treated with lime, nitrogen, or lime plus nitrogen in a 75-day glasshouse experiment. Lime and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
106
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 57 publications
9
106
2
Order By: Relevance
“…Several studies have been published investigating the impact of plant species on bacterial communities (Westover et al, 1997;Kennedy et al, 2005;Marschner et al, 2004Marschner et al, , 2005Phillips et al, 2006). However, most of them dealt with relatively small pots and short cultivation time.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published investigating the impact of plant species on bacterial communities (Westover et al, 1997;Kennedy et al, 2005;Marschner et al, 2004Marschner et al, , 2005Phillips et al, 2006). However, most of them dealt with relatively small pots and short cultivation time.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is unknown but both are direct effects of fertilizer itself, and changes in the plant community and litter associated with fertilizers could be involved (Donnison et al 2000;Manning et al 2006). Fungal DNA profiles can also undergo a reduction in diversity in response to fertilizer (Allison et al 2007), but others found that the bacterial communities (but not fungi) can be altered by high rates of fertilizer (Gray et al 2003;Kennedy et al 2004Kennedy et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Although pasture production and quality improve with N fertilizer, below-ground diversity may decrease as the quantity and quality of litter entering the soil food web changes (Donnison et al 2000). In grassland soils, both the bacterial and fungal communities may experience a reduction in diversity in response to N fertilizer (Kennedy et al 2004(Kennedy et al , 2005. Further, both soil microbial biomass and the soil fungal:bacterial ratio generally decrease with N fertilizer, (Bardgett et al 1999Grayston et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that addition of DOMs was an important driving force to stimulate the growth of bacteria especially those responsible for the [35][36][37][38]. The profiling analysis of microbial communities can contribute to identify the members of potential PAH-degrading microbial consortia and understand the patterns of microbial responses to external stimuli in polluted soils [14,39]. In this s t u d y, a l l n a h c l o n e s w e r e a f f i l i a t e d w i t h i n Gammaproteobacteria and Betaproteobacteria.…”
Section: Discussionmentioning
confidence: 99%